Stockholms bokbindare 1460-1880. Bd 2, Tiden från omkring 1700 till 1880 - Hedberg, Arvid (Stockholm : [Nordiska museet], 1960)
Summary: Stockholm bookbinders c. 1700-1880.
Keywords: bokbindare; hantverkare; kirjansitojat; käsityöläiset; Ruotsi; Stockholm; Sverige; Tukholma